What will our children do when we are gone? Italian legislature does not tackle the worries of parents of disabled children. Reflections on disability. - Karaboue, Michele Ahmed Antonio; Milone, Valentina; La Casella, Giorgia Viola; Ferrara, Michela; Delogu, Giuseppe; Di Fazio, Nicola; Volonnino, Gianpietro (Medicina Historica, 2022)
Background: Over the last fifty years the concept of health has passed, hence from a humanitarian and charitable approach to an approach based on respect for human rights and the removal of obstacles and discrimination. This is an important change because of the need for legislature to address the necessities of disabled people. Legislation analysis: The Italian Law n. 112/2016 recognized the importance of a more ‘human’ relationship between seriously disabled people and the context in which they live. The law gave the power to severely disabled individuals to decide whether to continue to live in their apartment alone, or sharing the own apartments with others, or move to an assisted living structure, after their parents’ death. Conclusion: Unfortunately, a strong limitation of the law is that it is mainly designed only in favor of severely disabled individuals, thus excluding other people who have also the need and the right to better living conditions, and the choice of trust, which is expensive and not available to all families. This review aims to make a revision of national and international legislation on disability, underlining lights and shadows to provide insights for future implementations and improvements.